2012
DOI: 10.1158/0008-5472.can-11-2883
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum Biomarker Signatures Associated with Pancreatic Cancer

Abstract: Pancreatic cancer is an aggressive disease with poor prognosis, due, in part, to the lack of disease-specific biomarkers that could afford early and accurate diagnosis. With a recombinant antibody microarray platform, targeting mainly immunoregulatory proteins, we screened sera from 148 patients with pancreatic cancer, chronic pancreatitis, autoimmune pancreatitis (AIP), and healthy controls (N). Serum biomarker signatures were derived from training cohorts and the predictive power was evaluated using independ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
115
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 45 publications
6
115
0
Order By: Relevance
“…A panel of markers reflecting different patho-physiological processes involved in different pancreatic diseases will almost certainly be required for diagnosis, prognosis and assessment of the efficacy of interventions. The collagen turnover biomarkers may potentially combine with other tools (such as a recently described 25 protein platform based on the role of the immune system in PDAC [38]) and add additional information that may improve PC outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A panel of markers reflecting different patho-physiological processes involved in different pancreatic diseases will almost certainly be required for diagnosis, prognosis and assessment of the efficacy of interventions. The collagen turnover biomarkers may potentially combine with other tools (such as a recently described 25 protein platform based on the role of the immune system in PDAC [38]) and add additional information that may improve PC outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Wingren et al pointed out that the individual biomarkers that have been identified for pancreatic cancer [e.g., C-reactive protein (CRP), haptoglobin, IGF-binding protein (IGFBP)-1 and CA 19-9] all lack specificity, as they are elevated in both nonmalignant conditions (e.g., pancreatitis and acute cholangitis) and other gastrointestinal cancers (e.g., gastric cancer and colorectal cancer) (59). Thus, the authors set out to identify a serum protein biomarker signature.…”
Section: Ii- Biomarker Signaturesmentioning
confidence: 99%
“…Typically these methods focus on selecting a subset of features (e.g. biomarkers) that maximize predictive accuracy, such as support vector machine (SVM) with backward feature selection (73) or partial area under the curve (AUC) (74), algorithms. However, recent research using simulated data implies that for biomarker discovery the best feature-ranking methods also estimate false discovery rates, which are not calculated by SVM and AUC algorithms.…”
Section: S)mentioning
confidence: 99%